(untitled) (Research, Society and Development, 2022)
The techniques and procedures derived from forensic expertise are used in forensic dentistry, comprising a variety of methods to identify a living, deceased person or their mortal remains. Thus, the objective of this research was to identify the main methods of human identification performed by forensic dentistry in Brazil. This is an integrative review, carried out in the databases Medical Literature Analysis and Retrieval System Online (Medline), Latin American and Caribbean Literature in Health Sciences (Lilacs) and Scientific Electronic Library Online (Scielo), in the month of January 2022. The following methods were identified: rugoscopy, cheiloscopy, imaging, papilloscopy, clinical and orthodontic documentation. The use of each technique depends on the individuality of each case, in order to enable the comparison of records before and after death, which implies the maintenance of an organized database by dental surgeons.